2015
DOI: 10.1016/j.tsf.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sticking Re-Ir coating for glass molding process

Abstract: a b s t r a c t a r t i c l e i n f oThe sticking of glass to the dies is a critical problem in glass molding process which limits the quality of products and lifespan of mold. Three kinds of protective coatings, including monolayer Re, Ir and Re/Ir multilayer were designed to mitigate the sticking and to improve the lifespan of mold. The interaction between barium crown optical glass and WC/Co mold materials (Co-10 at. %) with these three protective coatings was investigated. The results demonstrated that ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Thus, coating is often used for extending mold life and thereby leading to the cost reduction of the molded optical products. There are mainly three types of coatings available in the market, namely, ceramic coating (TiAlN, CrN, TiBCN or TiBC) [63], noble metal coating (Pt/Ir [64,65] and Re/Ir [66,67]), and carbon coating (diamondlike coating, amorphous carbon coating) [68]. Ceramic coatings have been widely used in making machining tools, and therefore are straightforward to apply to PGM molds.…”
Section: Mold Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, coating is often used for extending mold life and thereby leading to the cost reduction of the molded optical products. There are mainly three types of coatings available in the market, namely, ceramic coating (TiAlN, CrN, TiBCN or TiBC) [63], noble metal coating (Pt/Ir [64,65] and Re/Ir [66,67]), and carbon coating (diamondlike coating, amorphous carbon coating) [68]. Ceramic coatings have been widely used in making machining tools, and therefore are straightforward to apply to PGM molds.…”
Section: Mold Materialsmentioning
confidence: 99%
“…Noble metal coatings, especially the Pt/Ir alloy coating, can avoid such adhesion [64,65]. Nevertheless, it has been found that the Pt/Ir layer is not stable [66,67], and that the substrate material can diffuse into the coating layer and reduce its quality. However, the noble metal coating of Re/Ir demonstrates very stable properties [66] and low wetting angle among various coating materials [67].…”
Section: Mold Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that protective coatings can effectively improve the anti-sticking and anti-wear performance of forming dies [10][11][12][13][14][15][16][17][18]. Precious metal coatings are widely used in molding…”
Section: Introductionmentioning
confidence: 99%
“…Following an increase in W content, the annealed coating showed a mixed face-centered cubic (f.c.c) and hexagonal close-packed (h.c.p) matrix. The large volume fraction of h-WN phases seriously weakened the coating strengthening effect and caused an obvious drop in hardness.Coatings 2020, 10, 198 2 of 11 manufacturing due to their excellent anti-sticking and anti-oxidation properties [10][11][12], but they are also expensive for their wide industrial applications. Diamond-like carbon (DLC) films exhibit good self-lubrication and anti-wear performance, however, their poor thermal stability greatly limits any molding application [13,14].…”
mentioning
confidence: 99%